Evaluation of Baghdad water quality using Fuzzy logic - Gahfil, Jabbar A.; Ali , Huda Abdulateef (Iraqi Journal of Science, 2022)
Fuzzy measures are considered important tools to solve many environmental problems. Water pollution is one of the environmental problems, which has negatively effect on the health of consumers. In this paper, a mathematical model is proposed to evaluate water quality in the distribution networks of Baghdad city. Fuzzy logic and fuzzy measures have been applied to evaluate water quality with respect to chemical and microbiological contaminants. Our results are evaluate water pollution of some chemical and microbiological contaminants, which are difficult to evaluation through traditional methods.